GPR39 agonist TC-G 1008 ameliorates IL-1β-induced chondrocyte senescence. Issue 1 (4th December 2019) - Lu, Huading; Wang, Dawei; Li, Huizi; Zhong, Junlong; Lin, Yimin; Xu, Xianghe; Wang, Bin
Abstract: Aging-related osteoarthritis (OA) is the most common type of arthritis. Chondrocyte senescence has been linked with the pathogenesis of OA. Here, we examined the expression of GPR39 in chondrocytes and its modulatory effect on IL-1β-induced cellular senescence. We show that GPR39 is moderately expressed in human chondrocytes and its expression is repressed by the pro-inflammatory cytokine IL-1β. The GPR39 agonist TC-G 1008 mitigates IL-1β-induced chondrocyte senescence. Mechanistically, we show that TC-G 1008 mitigates IL-1β-induced cell cycle arrest at G1 phase by suppressing the expression of p53, p21, PAI-1, and K382 acetylation of p53. Moreover, we show that TC-G 1008 treatment restores IL-1β-induced inhibition of SIRT1 and the silencing of SIRT1 abolishes the function of TC-G 1008 on p53 acetylation and senescence, suggesting that the function of GPR39 signaling is mediated by SIRT1 in chondrocytes. Altogether, our findings implicate that the activation of GPR39 signaling ameliorates IL-1β-induced chondrocyte senescence and the GPR39 agonist TC-G 1008 could have the potential to modulate aging-associated OA.